2021
DOI: 10.1029/2020gl092126
|View full text |Cite
|
Sign up to set email alerts
|

Satellite Remote Sensing of Herring (Clupea pallasii) Spawning Events: A Case Study in the Strait of Georgia

Abstract: In this proof‐of‐concept study, we show how satellite remote sensing can be used to detect and monitor Pacific herring spawning events in the Strait of Georgia (SoG), British Columbia, Canada. Multi‐sensor medium‐resolution (∼300 m) and high‐resolution (3–30 m) images reveal bright waters in the SoG due to high concentrations of herring milt from multiple spawning events. The milt‐infused waters lead to enhanced reflectance with unique spectral characteristic that can be distinguished from other optically acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Satellite remote sensing provides an effective way to capture spatio-temporal continuous environmental data and to provide a holistic view of the influencing variables of fishery resources. Previous studies have demonstrated that remote sensing can be used for investigating lake fishery resources, assessing fish habitats, and forecasting fish situations (Lucas and Baras, 2000;Herold et al, 2007;Grimm et al, 2016;Qi et al, 2021). In particular, remote sensing allows large-scale, real-time, and dynamic monitoring of the water environment variables, such as chlorophyll-a concentrations (Chla), Secchia disk depth (SDD), suspended particulate matter (SPM), and other water quality parameters (Kutser, 2004;Awad, 2014;Cao et al, 2017;Hou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Satellite remote sensing provides an effective way to capture spatio-temporal continuous environmental data and to provide a holistic view of the influencing variables of fishery resources. Previous studies have demonstrated that remote sensing can be used for investigating lake fishery resources, assessing fish habitats, and forecasting fish situations (Lucas and Baras, 2000;Herold et al, 2007;Grimm et al, 2016;Qi et al, 2021). In particular, remote sensing allows large-scale, real-time, and dynamic monitoring of the water environment variables, such as chlorophyll-a concentrations (Chla), Secchia disk depth (SDD), suspended particulate matter (SPM), and other water quality parameters (Kutser, 2004;Awad, 2014;Cao et al, 2017;Hou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%